2018
DOI: 10.3389/fmicb.2018.02295
|View full text |Cite
|
Sign up to set email alerts
|

New Biocide Foam Containing Hydrogen Peroxide for the Decontamination of Vertical Surface Contaminated With Bacillus thuringiensis Spores

Abstract: Despite scientific advances, bacterial spores remain a major preoccupation in many different fields, such as the hospital, food, and CBRN-E Defense sector. Although many disinfectant technologies exist, there is a lack for the decontamination of difficult to access areas, outdoor sites, or large interior volumes. This study evaluates the decontamination efficiency of an aqueous foam containing hydrogen peroxide, with the efficiency of disinfectant in the liquid form on vertical surfaces contaminated by Bacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Whether the hydrogen peroxide is applied in liquid form, vapor form or even a foam affects its efficacy. A study by Le Toquin et al [ 53 ] found hydrogen peroxide added to foam to be more effective at higher temperatures at inactivating Bacillus thuringiensis spores compared to its liquid counterpart. However, the temperature sensitivity of the foam affects the contact time required; when applied to a vertical surface, the biocide was effective after 25 min at 30 °C but not at 4 °C, for which 2 h and 30 min was calculated as required for effective disinfection [ 53 ].…”
Section: Hydrogen Peroxidementioning
confidence: 99%
See 1 more Smart Citation
“…Whether the hydrogen peroxide is applied in liquid form, vapor form or even a foam affects its efficacy. A study by Le Toquin et al [ 53 ] found hydrogen peroxide added to foam to be more effective at higher temperatures at inactivating Bacillus thuringiensis spores compared to its liquid counterpart. However, the temperature sensitivity of the foam affects the contact time required; when applied to a vertical surface, the biocide was effective after 25 min at 30 °C but not at 4 °C, for which 2 h and 30 min was calculated as required for effective disinfection [ 53 ].…”
Section: Hydrogen Peroxidementioning
confidence: 99%
“…A study by Le Toquin et al [ 53 ] found hydrogen peroxide added to foam to be more effective at higher temperatures at inactivating Bacillus thuringiensis spores compared to its liquid counterpart. However, the temperature sensitivity of the foam affects the contact time required; when applied to a vertical surface, the biocide was effective after 25 min at 30 °C but not at 4 °C, for which 2 h and 30 min was calculated as required for effective disinfection [ 53 ]. Due to the ability of vapor and foam-based biocides to decontaminate difficult to reach surfaces, they may be more beneficial for the decontamination of whole rooms, for example patient rooms in hospitals.…”
Section: Hydrogen Peroxidementioning
confidence: 99%
“…In the future, it would be interesting to improve the foam stability by adding co-surfactants or polymers as already studied for foam flows in nuclear decontamination to try to improve further the spores’ removal action of the foam by increasing the foam friction mechanism and higher foam viscous stress [ 32 ]. Moreover, foams are already used to decontaminate static vertical surfaces from spores by using disinfecting formulations [ 16 ]. The next step in this study would be in the same way to combine the mechanical action of the foam flows with a chemical action to clean and decontaminate in the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, APGs are biosurfactants produced from vegetable oils and starch (plant-derived feedstock chemicals) suitable for cleaning applications in food industries, but also already widely used for various applications in personal care products. Moreover, APG foams have been shown to be very efficient for spores decontamination under static conditions on vertical surfaces [ 16 ]. We studied two different APGs known to be good cleansing and foaming agents: decyl glucoside (DG) and lauryl glucoside (LG) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…DSM 5815 was prepared as described by Wood et al [30]. The Bt concentration and the protocol used for deposition on the substrates were as described by Le Toquin et al [31]. A bacterial suspension of Bt spores was prepared in distilled water at a concentration of 2 × 10 8 CFU•mL −1 .…”
Section: Biological Decontamination Experimentsmentioning
confidence: 99%